Is the WTO a World Tax Organization? : A Primer for WTO Rules for Policy Makers - Daly, Michael (Washington, D.C. : International Monetary Fund, 2016)
This paper examines the extent to which World Trade Organization (WTO) rules impinge on policymakers' freedom to formulate tax policies. It provides an overview of both the economic rationale for WTO rules concerning taxation and the provisions of the main WTO agreements concerning border taxes and internal taxes (direct as well as indirect). It also points out some tax anomalies and inconsistencies in these rules, and how the rules have evolved as a consequence of the interpretation of the WTO agreements by its Dispute Settlement Body and the latter's rulings in connection with several disputes over taxes affecting trade. As WTO Members will undoubtedly want to avoid having their tax policies successfully challenged in the WTO, the paper provides some guidance concerning the design of tax policy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet